KONSEP ECOTOURISM DALAM MENCIPTAKAN PARIWISATA BERKELANJUTAN (Desa Wisata Patihan)): (STUDY ON PATIHAN TOURISM VILLAGE) - Agung Sulistyo; David Christyanta; Edy Suharyono; Aneke Rahmawati; Sumiyar Mahanani; Farah Diana Djamil; Dwi Agus Kristianto (Pusat Perencanaan dan Pengembangan Kepariwisataan, 2023)
Ecotourism is a sustainable tourism activity that utilizes nature and displays environmentally friendly tourist attractions. Ecotourism has several parameters for managing tourist attractions. These parameters include travel to the location, minimizing negative impacts, appreciation of local culture, economic impact on society, environmental awareness, economic benefits through conservation and freedom of management. This research aims to analyze the application of the ecotourism concept. A qualitative descriptive use to investigate the Patihan tourist village. The informants in this research were the Patihan tourist village manager, the surrounding community and tourists. The Miles Huberman method to analyze the data. The research results show that the ecotourism concept has yet to be fully implemented by tourism village managers. Instruments providing an economic impact on society, environmental concerns, and economic benefits through conservation have not been fully implemented. Attention to developing tourist villages through ecotourism needs to create sustainable tourism.